wakalah bil ujrah Implementation of The Wakalah Bil Ujrah Agreement in Sharia Financial Technology (Fintech) Services In Indonesia Reviewed From the Specific Specificity of Legal Certainty and Consumer Protection - Yudhanto, Genesi; khayat, khayatudin; David, David Novan Setyawan (Dinasti Research, 2026)
The development of Sharia financial technology (fintech) services in Indonesia is driving the transformation of Sharia contracts into digital-based systems, one of which is the wakalah bil ujrah contract. This contract forms the basis of the legal relationship between platform providers and service users in financing mechanisms, fundraising, and other financial intermediary services. This study aims to analyze the legal construction and implementation of the wakalah bil ujrah contract in Sharia fintech in Indonesia and assess its compliance with the principles of legal certainty and consumer protection. The research method used is normative legal research with a statutory and conceptual approach. Primary legal materials include laws and regulations, including Law Number 21 of 2008 concerning Sharia Banking, Law Number 8 of 1999 concerning Consumer Protection, and regulations and supervision by the Financial Services Authority. Furthermore, this study also refers to the fatwa of the National Sharia Council of the Indonesian Ulema Council regarding the wakalah bil ujrah contract. Secondary legal materials, including literature, scientific journals, and relevant legal doctrines, were analyzed qualitatively. The results of the study indicate that, normatively, the wakalah bil ujrah contract in Islamic fintech has an adequate legal basis through sectoral regulations and Islamic fatwas. However, in practice, several problems remain, including the unclear construction of legal relationships between parties in digital contracts, the potential use of standard clauses that are detrimental to consumers, and the suboptimal transparency of risks and responsibilities of platform operators. These conditions indicate that the implementation of the wakalah bil ujrah contract does not fully reflect the principles of legal certainty and consumer protection as mandated by the national legal system. Therefore, regulatory harmonization, strengthening of supervisory mechanisms, and standardization of Sharia-based digital contracts are needed to ensure legal certainty and consumer protection in the implementation of Islamic fintech in Indonesia.